ICT and educational applications - Lucas Castro Martínez (Centro de Estudios Financieros, 2016)
The information and communication technologies (ICT) are included in almost all areas of our lives, and particularly have erupted with great force in education, making that are imposing new forms, processes and communication systems. In education today, both from the point of view of the teacher as the learner, it is almost imperative to know how to surf the net, to search for information, send and receive e-mails, communicate and work collaboratively in real time or deferred with others through the various tools out there for it, as well as various social networks to share knowledge to create documents on the web in blogs, wikis, etc. These are the new skills that are becoming increasingly necessary in the «new era of communication». In this article it has been briefly reviewed the various ICT resources it could been found on the net and why and how to use them from the point of teaching seen.